Associations of Serum Biomarkers of Fruit and Vegetable Intake With the Risk of Cause–Specific Mortality and All–Cause Mortality: A National Prospective Cohort Study - Pu, Liyuan; Zhang, Ruijie; Wang, Xiaojie; Zhao, Tian; Sun, Hongpeng; Han, Liyuan (Frontiers in Nutrition, 2022)
Objective: The purpose of this study was to evaluate the associations of serum biomarkers of fruit and vegetable intake (vitamin C and carotenoids) with cause-specific mortality and all-cause mortality in a nationally representative sample of US adults. Methods: We analyzed data from 15,971 participants from the National Health and Nutrition Examination Survey III (1988-1994). Cox proportional hazards models with restricted cubic spline terms was used for the analysis. Results: During 266,747 person-years of follow-up, 5,104 deaths occurred, including 1,665 deaths from cardiovascular disease, 1,294 deaths from heart disease, 371 deaths from cerebral disease and 1,069 deaths from cancer. Hazard ratios (95% confidence intervals) (HR [95%CIs]) for the associations of the highest quintiles of serum vitamin C concentration, total carotenoid concentration and composite biomarker score with cancer mortality, compared with the lowest quintiles, were 0.52 (0.38-0.70), 0.54 (0.41-0.71)and 0.45 (0.36-0.58), respectively. After multivariate adjustment, higher serum concentrations of vitamin C (HR per standard deviation [SD], 0.83; 95% CI, 0.74-0.92] and total carotenoids (HR per SD, 0.85; 95%CI, 0.74-0.97) were associated with a lower cancer mortality rate. The change for each one SD in the composite biomarker score, equivalent to a 0.369 times/month difference in carrot intake, gave an HR of 0.79 (0.69-0.90) for cancer mortality. Conclusions: In this national cohort, higher serum concentrations of vitamin C and total carotenoids and composite biomarker scores were associated with a lower risk of cancer mortality. Our findings support an increase in dietary fruit and vegetable intake as a primary prevention strategy for cancer mortality.